1985
DOI: 10.1017/s0022112085003007
|View full text |Cite
|
Sign up to set email alerts
|

Observations of bispectra of shoaling surface gravity waves

Abstract: Aspects of the nonlinear dynamics of waves shoaling between 9 and 1 m water depths are elucidated via the bispectrum. Bispectral-signal levels are generally high, indicating significant nonlinear coupling. In 9 m depth, the biphases of interactions involving frequencies at, and higher than, the peak of the energy spectra are suggestive of Stokes-like nonlinearities (Hasselman, Munk & MacDonald 1963). Further shoaling gradually modifies these biphases to values consistent with a wave profile that is pitched sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
302
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(332 citation statements)
references
References 24 publications
27
302
1
2
Order By: Relevance
“…Swash, the time-varying position of the shoreward edge of water on a beach, results from standing waves, formed by the reflection of incident waves off the shoreline [e.g., Miche, 1951;Elgar and Guza, 1985;Guza and Thornton, 1985;. There is still considerable debate as to how swash is related to environmental conditions such as local beach slope and offshore wave characteristics, despite the numerous studies that have been devoted to this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Swash, the time-varying position of the shoreward edge of water on a beach, results from standing waves, formed by the reflection of incident waves off the shoreline [e.g., Miche, 1951;Elgar and Guza, 1985;Guza and Thornton, 1985;. There is still considerable debate as to how swash is related to environmental conditions such as local beach slope and offshore wave characteristics, despite the numerous studies that have been devoted to this subject.…”
Section: Introductionmentioning
confidence: 99%
“…The generation and amplification of these harmonics were studied and investigated by several observational and numerical studies (4)(5)(6)(7)(8). Results showed that these harmonics are bound with the spectral peak (8)(9)(10)(11). The second and third peaks of energy spectrum on two and three times of spectral peak frequency are very usual for field measurements (12,13).…”
Section: Introductionmentioning
confidence: 92%
“…Elgar and Guza, 1985), and induce radiation of long waves at the 'beat' frequencies of the incident wave field, generally referred to as 'surfbeat' (e.g., Munk, 1949).…”
Section: Nonlinearity In Shallow Watermentioning
confidence: 99%
“…In general triad interactions transfer energy from the incident wave components to higher-(e.g., harmonic) and lower-(e.g., infra-gravity) frequency components (see, e.g., Freilich and Guza, 1984;Elgar and Guza, 1985;Agnon et al, 1993;Kaihatu and Kirby, 1995;Agnon and Sheremet, 1997;Herbers and Burton, 1997;Ruessink, 1998;Kaihatu, 2001;Sheremet et al, 2003;Janssen et al, 2003, and many others). These interactions not only broaden the frequency spectrum in shallow water, but also phase-couple the spectral components, causing the characteristic steepening and pitching forward of nearbreaking wave crests.…”
Section: Nonlinearity In Shallow Watermentioning
confidence: 99%